A method for preparing a completely degradable antibacterial, antiviral and wash-resistant fabric
By grafting isocyanate groups and hyperbranched polymers on the surface of the fabric and modifying quaternary ammonium salts at its ends, the problem of poor washing resistance of existing antibacterial and antiviral fabrics is solved, and high-efficiency antibacterial and antiviral properties and good washing resistance are achieved, and it is suitable for reusable bioprotective textiles.
Patent Information
- Application Number
- CN202211247780.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The existing hyperbranched polymer-modified antibacterial and antiviral fabrics have poor washing resistance and cannot meet the requirements of reusability. At the same time, modification methods such as potassium permanganate damage the fibers greatly and cannot meet the environmental protection requirements.
The fabric surface is activated by grafting the isocyanate groups, the hyperbranched polymer is grafted, and quaternary ammonium salt modification is carried out at its end to form a covalent bond structure to improve antibacterial and antiviral properties and wash fastness.
It realizes the efficient antibacterial and antiviral properties of the fabric, and has good washing resistance and durability, and has little damage to the fibers and can be completely degraded. It is suitable for reusable bioprotective textiles.
Smart Images

Figure CN116556054B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of antibacterial fabrics, and in particular relates to a method for preparing a completely degradable antibacterial, antiviral and wash-resistant fabric. Background Art
[0002] Compared with linear polymers, hyperbranched polymers can be synthesized in one step, at low cost, and have excellent fluidity, low molecular entanglement, low viscosity, high fluidity and excellent sustained release ability. In addition, hyperbranched polymers have a highly branched three-dimensional molecular structure, and the ends contain rich active groups, so it is easy to modify them with antibacterial and antiviral functional groups. In particular, degradable hyperbranched polymers based on materials such as polylysine with biomimetic structures have high biosafety and degradability, and have broad application prospects in the development of antibacterial and anti-toxic textiles. However, the surface of hyperbranched polymers lacks high grafting active functional groups for groups such as hydroxyl groups, and is only fixed to the fiber surface by electrostatic adsorption, so it is not resistant to surfactants, detergents, decontamination agents, etc., and has poor washing resistance, which cannot meet the requirements of reusable antibacterial and antiviral textiles. The existing methods for improving binding fastness mainly include methods such as forming chemical bonds between antibacterial agents and fabrics or forming films on the surface. Hyperbranched polymers are extremely water-soluble, and it is difficult to form a stable cross-linked structure between molecules, so their load fastness can only be improved by covalent grafting.
[0003] The prior art ("Preparation of Hyperbranched Polymers and Functional Modification of Cotton Fibers", Zhang Feng, PhD thesis of Soochow University, May 1, 2009) discloses: cotton fabrics are treated by impregnation with an aqueous solution of a hyperbranched polymer quaternary ammonium salt HBP-HTC to impart antibacterial properties to the fabrics. Test results show that the antibacterial rates of HBP-HTC-finished cotton fabrics against S. aureus and E. coli are 99.92% and 99.66%, respectively; after washing 20 times, the antibacterial rate is still 99.00%, reflecting a certain durability. However, since there is no covalent bond between the hyperbranched polymer quaternary ammonium salt and the fabric, the fabric is not resistant to washing and cannot be used for reusable antibacterial and antiviral textiles, which greatly limits its application in antibacterial and antiviral biological protective textiles, especially in clothing and household textiles. In addition, the hyperbranched polymer loses its coupling activity after quaternization and cannot achieve covalent bonding. Therefore, many studies have modified the surface of cotton and other materials by potassium permanganate, sulfuric acid, etc. to improve their reactivity, and then react with hyperbranched polymers to achieve covalent bonding. However, this method is extremely damaging to the material, especially natural fibers such as cotton fibers, which lose their strength after being treated with potassium permanganate, and basically lose their value for consumption. In addition, the treatment process is seriously polluting and cannot meet environmental protection requirements. This method is not applicable to hyperbranched polymer quaternary ammonium salts, so the antibacterial and especially antiviral properties cannot meet the requirements of biological protection.
[0004] Therefore, it is of great significance to study novel hyperbranched polymer-modified antibacterial and antiviral fabrics based on covalent grafting methods with low fiber damage and washing resistance. Summary of the invention
[0005] The invention of the present application aims to provide a method for preparing a fabric modified by a hyperbranched polymer with a quaternary ammonium salt grafted at the end, which is completely degradable and has low fiber damage, so as to give the fabric strong antibacterial and antiviral functions and washability without affecting the fabric strength and biological safety. The invention firstly activates the fabric by grafting isocyanate groups, then grafts the hyperbranched polymer onto the fabric surface, and finally modifies the terminal groups thereof with quaternary ammonium salts, thereby improving the antibacterial and antiviral properties and washability of the fabric.
[0006] The specific reaction principle is as follows: the present invention firstly utilizes the high reactivity of the siloxane group to undergo a grafting reaction with the hydroxyl group, keto group, amino group, etc. on the surface of the fabric, thereby grafting a highly reactive isocyanate group on the surface of the fabric. The group has extremely high reactivity with the amino group and the hydroxyl group, and can react with the amino group and the hydroxyl group at the end of the hyperbranched polymer. Therefore, the hyperbranched polymer can be grafted onto the surface of the fabric through a simple heating reaction, and the isocyanate coupling agent plays a coupling role in the above reaction process; finally, the fabric modified with the hyperbranched polymer is immersed in a quaternary ammonium salt small molecule solution. The reaction is relatively easy, and the reaction can be completed quickly by simple heating, and the grafting efficiency is relatively high.
[0007] The present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a completely degradable antibacterial, antiviral and wash-resistant fabric, the preparation method comprising the following steps:
[0009] S1, dissolving a siloxane coupling agent with an isocyanate group in an organic solvent to obtain a siloxane coupling agent solution, then immersing a fabric in the siloxane coupling agent solution, adding water for treatment, and then drying to obtain a fabric with an isocyanate group grafted on the surface;
[0010] S2, dissolving a hyperbranched polymer in water to obtain a hyperbranched polymer solution, immersing the fabric with the surface grafted with isocyanate groups in the hyperbranched polymer solution for treatment, and then drying to obtain a fabric modified with the hyperbranched polymer;
[0011] S3, dissolving an alkoxy quaternary ammonium salt in water to obtain an aqueous solution of the alkoxy quaternary ammonium salt, immersing the hyperbranched polymer-modified fabric in the aqueous solution of the alkoxy quaternary ammonium salt for treatment, and then drying to finally obtain a hyperbranched polymer-modified fabric.
[0012] In the present invention, the bath ratio refers to the ratio of the mass of the impregnated fabric to the volume of the impregnation solution.
[0013] Furthermore, the fabric is selected from cotton, silk, wool, polylactic acid fabric, polycaprolactone fabric or a blended fabric of two or more of the aforementioned fabrics.
[0014] Furthermore, in the above preparation method, the siloxane coupling agent with an isocyanate group in step S1 is one or more of isocyanatepropyltrimethoxysilane, isocyanatepropylmethyldiethoxysilane, isocyanatepropylmethyldimethoxysilane, diisocyanatedimethylsilane and isocyanatepropyltriethoxysilane, preferably isocyanatepropyltriethoxysilane; and / or, the organic solvent is an alcohol solvent, preferably selected from methanol and / or ethanol, more preferably ethanol.
[0015] Furthermore, in the above preparation method, in step S1, the concentration of the siloxane coupling agent in the siloxane coupling agent solution is 0.1-10wt%, preferably 0.5-5wt% or 1-4.5wt%, more preferably 3-4wt%.
[0016] In step S1, the grafting rate or grafting amount of isocyanate groups in the fabric with isocyanate groups grafted on the surface is 60% to 80%.
[0017] The isocyanate group content is determined by reacting the fabric with excess di-n-butylamine to generate substituted urea, titrating the excess di-n-butylamine with a standard hydrochloric acid solution, and using bromocresol green as an indicator until the color of the indicator changes from green to yellow.
[0018]
[0019] NCO%=(V0-V1)*C*4.202 / m
[0020] V0: Volume of HCl consumed by blank sample, mL
[0021] V1: Volume of HCl consumed by the sample, mL
[0022] C: Concentration of HCl standard solution, mol / L
[0023] m: sample size, g.
[0024] Reaction equation of the present invention is as follows:
[0025]
[0026] In the reaction equation, HBP refers to a hyperbranched polymer; and the quaternary ammonium salt small molecule refers to an alkoxy quaternary ammonium salt.
[0027] Furthermore, in the above preparation method, in step S1, the treatment temperature is 20-90°C, preferably 30-80°C, and more preferably 50-60°C; the treatment time is 10-180min, preferably 20-120min, more preferably 30-90min, for example, about 60min; and / or, in step S1, the volume ratio of water to the organic solvent is 1:1-1:5, preferably 1:1-1:4, more preferably 1:1.5-1:2.5, for example, 1:2.
[0028] Further, in the above preparation method, in step S2, the hyperbranched polymer is a degradable hyperbranched polymer, preferably, the hyperbranched polymer is a degradable amino-terminated or hydroxy-terminated hyperbranched polymer. Preferably, the degradable hyperbranched polymer is selected from one or more of hyperbranched polylysine, hyperbranched lysine-arginine copolymer, and β-cyclodextrin grafted hyperbranched polyglycidyl ether, preferably amino-terminated hyperbranched polylysine and / or hyperbranched lysine-arginine copolymer, and the weight average molecular weight of the hyperbranched polymer is 1500-13000, preferably 2000-11000 or 3000-13000, for example 2000-5000 or 8000-11000.
[0029] Furthermore, in the above preparation method, in step S2, the concentration of the hyperbranched polymer in the hyperbranched polymer solution is 0.1-15wt%, preferably 0.2-12wt%, 0.3-10wt%, 0.4-8wt% or 0.5-5wt%, more preferably 1-3wt% or 2-4wt% or 2-3.5wt%, for example about 2wt%.
[0030] Furthermore, in the above preparation method, in step S2, the treatment temperature is 30-110°C, preferably 40-90°C, more preferably 50-70°C, for example, about 60°C, and the treatment time is 10-180min, preferably 20-120min, more preferably 30-90min, for example, about 60min; and / or, the bath ratio of the fabric with surface grafted isocyanate groups and the hyperbranched polymer solution is 0.1:50-5:50, preferably 0.5:50-2:50, for example, about 1:50.
[0031] Furthermore, in the above preparation method, in step S3, the alkoxy quaternary ammonium salt is an epoxy quaternary ammonium salt, which can be selected from 2,3-epoxypropyltrimethylammonium chloride and / or 2,3-epoxybutyltrimethylammonium chloride, preferably 2,3-epoxypropyltrimethylammonium chloride.
[0032] Furthermore, in the above preparation method, in step S3, the concentration of the alkoxy quaternary ammonium salt in the aqueous solution of the alkoxy quaternary ammonium salt is 0.1 to 15 wt %, preferably 0.5 to 5 wt %, more preferably 1 to 3 wt %; and / or,
[0033] In step S3, the molar ratio of the alkoxy quaternary ammonium salt to the hyperbranched polymer in step S2 is 100:1-2:1, preferably 90:1-4:1, 80:1-6:1, 70:1-8:1, 60:1-10:1, 50:1-10:1, 50:1-20:1, and more preferably 40:1-15:1; and / or, in step S3, the treatment temperature is 30-110°C, preferably 35-80°C, more preferably 40-60°C, and the treatment time is 10-180min, preferably 20-120min, more preferably 30-90min, for example 60min; and / or, in step S3, the bath ratio of the hyperbranched polymer-modified fabric and the aqueous solution of the alkoxy quaternary ammonium salt is 0.1:50-5:50, preferably 0.5:50-2:50, for example about 1:50.
[0034] Further, in step S1, step S2 and step S3, the drying includes (1) optional padding, (2) drying at 50-100°C, preferably 60-90°C, preferably 70-80°C for 10 minutes to 1 hour, preferably 20 to 50 minutes, preferably 25 to 40 minutes, for example, about 30 minutes and (3) baking at 100-120°C, preferably 105-110°C for 1-30 minutes, preferably 5 to 20 minutes, preferably 8 to 12 minutes, for example, about 10 minutes.
[0035] "Optional" means present or absent.
[0036] The hyperbranched polymers used in this application can be commercially available or prepared.
[0037] For example, in one embodiment, the hyperbranched lysine-arginine copolymer reaction equation is:
[0038]
[0039] Preferably, the hyperbranched lysine-arginine copolymer is prepared by the following steps:
[0040] L-lysine hydrochloride and KOH (molar ratio of 1.2:1-1:2) are ground in a mortar until thoroughly mixed, and then L-arginine is added (the molar ratio of L-lysine hydrochloride to L-arginine is 5:1-1:5, further 2:1 to 1:2). The above mixed slurry is added with paraffin oil (the molar ratio of paraffin oil to lysine can be 3:1-0.5:1), and then placed in a rotary evaporator, heated to 110-180°C for rotary evaporation reaction, and the water generated during the reaction is removed. After reacting for 20-60 hours, the reactor is cooled to room temperature. The reaction product is dissolved in deionized water (15-30wt, for example, about 20wt% concentration), acetone is added for precipitation and separation, and the separated product is dissolved in ethanol, and acetone is used for precipitation and separation again, and finally vacuum dried to obtain a hyperbranched lysine-arginine copolymer (weight average molecular weight of 3000-13000). In addition, for the preparation, reference may be made to the following literature: Qi Peng, Jianjun Zhu, Yongsheng Yu, Lee Hoffman & Xingkun Yang (2015) Hyperbranched lysine-arginine copolymer for gene delivery, Journal of Biomaterials Science, Polymer Edition, 26: 16, 1163-1177, DOI: 10.1080 / 09205063.2015.1080482.
[0041] In another embodiment, the hyperbranched polymer can be amino-terminated hyperbranched polylysine. For example, hyperbranched polylysine can be prepared by the following steps: under N2 protection, L-lysine methyl ester hydrochloride is heated to 150-200°C for reaction for 20-24h, the reaction product is dissolved in deionized water (the concentration can be 15-30wt%, for example 20wt%), and finally acetone is added for precipitation and separation, the separated product is dissolved in ethanol, acetone is used for precipitation and separation again, and finally vacuum drying is performed to obtain amino-terminated hyperbranched polylysine (weight average molecular weight 2000-5200) with a concentrated molecular weight.
[0042] The present invention also provides antibacterial, antiviral and wash-resistant fabrics prepared by the above-mentioned preparation method. The warp and weft strength loss rate of the fabric of the present invention is ≤10%; after washing 50 times, the antibacterial rate against Escherichia coli and Staphylococcus aureus is 99%, and the antiviral activity rate against influenza A virus is 98-99% (antibacterial detection standard: GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method"; antiviral detection standard: ISO 18184:2014 (E)).
[0043] The technical solution of the present invention has the following advantages:
[0044] The preparation method of the antibacterial, antiviral and washing-resistant fabric of the present invention comprises the following steps: firstly modifying the fabric with a siloxane coupling agent, grafting a highly reactive group isocyanate group to the fabric surface, then grafting a hyperbranched polymer to the fabric surface through a covalent grafting reaction (e.g., utilizing a padding and baking method), and finally immersing the fabric in an aqueous solution of an alkoxy quaternary ammonium salt, grafting the quaternary ammonium salt to the end of the hyperbranched polymer through a ring-opening polymerization reaction, and preparing a fabric modified with a hyperbranched polymer quaternary ammonium salt. The fabric modified with the hyperbranched polymer quaternary ammonium salt has excellent antibacterial and antiviral properties, and since the hyperbranched polymer is covalently bonded to the fabric, it has excellent washing fastness and washing fastness, good durability, and the mechanical properties remain substantially unchanged. The method of the present invention has little damage to the fabric fiber, can be completely degraded, solves the problems of low antibacterial and anti-toxic ability, low biological safety, poor durability and environmental pollution of the antibacterial and antiviral fabric, and is suitable for antibacterial and antiviral functional clothing and epidemic prevention textiles. In addition, this preparation method does not damage the mechanical properties of the fabric and has good wash resistance, and can be widely used in disposable or reusable biological protective textiles for clothing, household use, and epidemic prevention. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0046] Figure 1 is the infrared image of hyperbranched poly-lysine;
[0047] Figure 2 is an infrared image of the cotton fabric modified with the hyperbranched polylysine quaternary ammonium salt prepared in Example 1;
[0048] Figure 3 The SEM images of the cotton fabric fibers of Example 1, wherein (a) is the SEM image of the raw cotton fabric fibers of Example 1, and (b) is the SEM image of the cotton fabric fibers modified with the hyperbranched polylysine quaternary ammonium salt prepared in Example 1;
[0049] Figure 4 is a graph showing the change in strength in the warp and weft directions of the cotton fabric of Example 1 before and after treatment;
[0050] Figure 5 The infrared image of the hyperbranched poly-lysine quaternary ammonium salt-modified polylactic acid fabric prepared in Example 5;
[0051] Figure 6 1 and 2 are SEM images of the polylactic acid fabric fibers of Example 5, wherein (a) is the SEM image of the raw material polylactic acid fabric of Example 5, and (b) is the SEM image of the hyperbranched polylysine quaternary ammonium salt-modified polylactic acid fabric prepared in Example 5. DETAILED DESCRIPTION
[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Isocyanate propyl triethoxysilane, purchased from Hubei Jusheng Technology Co., Ltd., purity 97%, molecular weight 247.4;
[0054] β-Cyclodextrin grafted hyperbranched polyglycidyl ether was purchased from Xi'an Ruixi Biotechnology Co., Ltd., with a weight average molecular weight of about 3600.
[0055] Cotton fabric, commercially available;
[0056] Silk fabric, commercially available;
[0057] Wool fabrics, commercially available;
[0058] Polylactic acid fabric and polycaprolactone fabric were purchased from Anhui Fengyuan Biofiber Co., Ltd.
[0059] The polymer reaction equation of hyperbranched lysine-arginine copolymer is:
[0060]
[0061] Hyperbranched lysine-arginine copolymer reference was prepared according to the following method: L-lysine hydrochloride (10.958 g, 60.0 mmol) and 120 mmol KOH (molar ratio of 2:1) were ground in a mortar until thoroughly mixed, and then 60.0 mmol L-arginine (L-lysine hydrochloride and L-arginine molar ratio of 1:1) was added. 30 mmol paraffin oil was added to the above mixed slurry, and then placed in a rotary evaporator, heated to 160 ° C for rotary evaporation to remove the moisture generated during the reaction. After 50 hours of reaction, the reactor was cooled to room temperature. The reaction product was dissolved in deionized water (20 wt% concentration), acetone was added for precipitation and separation, and the separated product was dissolved in ethanol, precipitated and separated again with acetone, and finally vacuum dried to obtain a hyperbranched lysine-arginine copolymer (weight average molecular weight of 11000). Reference is made to the following literature: Qi Peng, Jianjun Zhu, Yongsheng Yu, Lee Hoffman & Xingkun Yang (2015) Hyperbranched lysine-arginine copolymer for gene delivery, Journal of Biomaterials Science, Polymer Edition, 26: 16, 1163-1177, DOI: 10.1080 / 09205063.2015.1080482.
[0062] The amino-terminated hyperbranched polylysine was prepared by the following method: under N2 protection, L-lysine methyl ester hydrochloride was heated to 180°C for reaction for 20 hours, the reaction product was dissolved in deionized water (20wt% concentration), and finally acetone was added for precipitation and separation. The separated product was dissolved in ethanol, precipitated and separated with acetone again, and finally vacuum dried to obtain amino-terminated hyperbranched polylysine with concentrated molecular weight (weight average molecular weight of 2000-5000, the molar amount was calculated according to the average molecular weight of 3500 in the following examples). Refer to Yang Z, Xi Y, Bai J, et al. Covalent grafting of hyperbranched poly-L-lysine on Ti-based implants achieves dual functions of antibacteria and promoted osteointegration in vivo[J]. Biomaterials, 2021, 269: 120534. The infrared image of the prepared hyperbranched polylysine is shown in Figure 1. Figure 1 shown.
[0063] In the following examples, the antibacterial testing standard is: GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method"; the antiviral testing standard is: ISO 18184:2014(E).
[0064] In the following examples, the isocyanate group content is determined by reacting fabric with excess di-n-butylamine to form substituted urea, titrating the excess di-n-butylamine with a standard hydrochloric acid solution, and using bromocresol green as an indicator until the color of the indicator changes from green to yellow.
[0065] Example 1
[0066] The preparation method of this embodiment comprises the following steps:
[0067] S1. 3 g of isocyanate propyl triethoxysilane was added to 100 mL of ethanol solution and mechanically stirred for 10 min to obtain an ethanol solution of isocyanate propyl triethoxysilane; 3 g of cotton fabric was immersed in the above solution, fully stirred for 10 min, 50 mL of deionized water was added, and finally the solution was heated to 60° C. and kept warm for 1 h; after the treatment was completed, the fabric was taken out by padding, dried at 80° C. for 30 min, and baked at 110° C. for 10 min to obtain a cotton fabric with surface grafted isocyanate groups (the grafting rate of isocyanate groups was 71%);
[0068] S2, dissolving 4.76g of amino-terminated hyperbranched polylysine (1.36mmol) in 150mL of deionized water to obtain an amino-terminated hyperbranched polylysine solution; immersing the cotton fabric with isocyanate groups grafted on the surface in step S1 in the above solution, treating at 60°C for 1h, drying at 80°C for 30min, and baking at 110°C for 10min to obtain an amino-terminated hyperbranched polylysine modified cotton fabric;
[0069] S3, 4.1g 2,3-epoxypropyltrimethylammonium chloride (27.2mmol) was dissolved in 150mL deionized water to obtain an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride, and the cotton fabric modified with hyperbranched polylysine in step S2 was immersed in the above solution, treated at 60°C for 1h, and finally dried at 80°C for 30min and baked at 110°C for 10min to obtain the cotton fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt.
[0070] Figure 2 This is an infrared image of the cotton fabric modified with the hyperbranched poly-lysine quaternary ammonium salt prepared in Example 1. Figure 2 It can be seen that after treatment, absorption peaks of C=O and CN appeared in the infrared image of the fabric. The above absorption peaks are unique absorption peaks of the amino group and amide bond (amide I and amide II) of hyperbranched polylysine, indicating that the hyperbranched polylysine quaternary ammonium salt was grafted onto the surface of the cotton fabric.
[0071] Figure 3 In the figure, (a) and (b) are respectively the SEM images of the raw cotton fabric fiber of the present embodiment and the SEM images of the prepared hyperbranched polylysine quaternary ammonium salt modified cotton fabric fiber. By comparison, it can be seen that the surface of the untreated cotton fiber is covered with spiral stripes, which is related to the longitudinal bending of the cotton fiber; the surface stripes of the cotton fiber after the surface is grafted with amino-terminated hyperbranched polylysine quaternary ammonium salt groups disappear, and the surface is covered with a layer of amino-terminated hyperbranched polylysine amine quaternary ammonium salt coating, and a cross-linked film also appears between the fibers, which shows that the method of the present embodiment has a higher loading efficiency.
[0072] The change of the strength in the warp and weft directions of the cotton fabric of Example 1 before and after treatment is shown in the figure Figure 4 As shown. Figure 4 It can be seen that the strength of cotton fabric after treatment not only did not decrease, but increased in both warp and weft directions. This may be because after the coupling reaction, the inside and surface of the yarn are adhered by the polymer, which increases the yarn cohesion and thus increases the strength of the fabric.
[0073] Depend on Figure 4 After calculation, it can be seen that the warp strength loss rate = (warp breaking strength of cotton fabric - warp breaking strength of cotton fabric after treatment) / warp breaking strength of cotton fabric = -4.5%, the weft strength loss rate = (weft breaking strength of cotton fabric - weft breaking strength of cotton fabric after treatment) / weft breaking strength of cotton fabric = -7.0%, that is, the warp and weft strength loss rates are both less than 10%.
[0074] The antibacterial properties of antibacterial fabrics before and after washing are important indicators for characterizing the durability of the antibacterial properties of fabrics. The test results are as follows: the antibacterial rate of the cotton fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared in this embodiment against Escherichia coli and Staphylococcus aureus can reach 99.99% before washing; after washing 50 times, the antibacterial rate is still maintained at 99.3%. After washing 50 times, the antiviral activity rate of the cotton fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared in this embodiment against influenza A virus reaches 99.14%. This shows that the cotton fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared by the method of this embodiment has excellent antibacterial and antiviral properties, and has good durability.
[0075] Example 2
[0076] The preparation method of this embodiment comprises the following steps:
[0077] S1. 3 g of isocyanate propyl triethoxysilane was added to 100 mL of ethanol solution and mechanically stirred for 10 min to obtain an ethanol solution of isocyanate propyl triethoxysilane; 3 g of silk fabric was immersed in the mixed solution, and 50 mL of deionized water was added after sufficient stirring for 10 min; the silk fabric was fully treated at 60° C. for 1 h, dried at 80° C. for 30 min, and baked at 110° C. for 10 min to obtain a silk fabric modified with an isocyanate group (the grafting rate of the isocyanate group was 68%);
[0078] S2, dissolving 4 g of β-cyclodextrin grafted hyperbranched polyglycidyl ether (1.11 mmol) in 150 mL of deionized water to obtain a β-cyclodextrin grafted hyperbranched polyglycidyl ether solution; immersing the fabric modified with isocyanate groups in step S1 in the above solution, treating at 60° C. for 1 h, drying at 80° C. for 30 min, and baking at 110° C. for 10 min to obtain a silk fabric modified with β-cyclodextrin grafted hyperbranched polyglycidyl ether;
[0079] S3. Dissolve 2.6 g of 2,3-epoxypropyltrimethylammonium chloride (17 mmol) in 150 mL of deionized water to obtain an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride, immerse the fabric modified with β-cyclodextrin grafted hyperbranched polyglycidyl ether in step S2 in the above solution, treat at 40° C. for 1 h, and finally dry at 80° C. for 30 min and bake at 110° C. for 10 min to obtain a silk fabric modified with β-cyclodextrin grafted hyperbranched polyglycidyl ether quaternary ammonium salt.
[0080] The test results are as follows: the antibacterial rate of the silk fabric modified by β-cyclodextrin grafted hyperbranched polyglycidyl ether quaternary ammonium salt prepared in this embodiment against Escherichia coli and Staphylococcus aureus can reach 99.98% before washing; after washing 50 times, the antibacterial rate is still maintained at 99.07%. After washing 50 times, the antiviral activity rate of the silk fabric modified by β-cyclodextrin grafted hyperbranched polyglycidyl ether quaternary ammonium salt prepared in this embodiment against influenza A virus is 98.1%. This shows that the silk fabric modified by β-cyclodextrin grafted hyperbranched polyglycidyl ether quaternary ammonium salt prepared by the method of this embodiment has excellent antibacterial and antiviral properties, and has good durability.
[0081] Example 3
[0082] The preparation method of this embodiment comprises the following steps:
[0083] S1, take 3g of isocyanate propyl triethoxysilane and add it to 100mL of ethanol solution and stir it mechanically for 10min to obtain an ethanol solution of isocyanate propyl triethoxysilane; immerse 3g of wool fabric in the above mixed solution, stir it thoroughly for 10min, then add 50mL of deionized water, and finally heat the solution to 60°C and keep it warm for 1h; after the treatment is completed, take out the fabric by padding, dry it at 80°C for 30min, and bake it at 110°C for 10min to obtain a wool fabric with surface grafted isocyanate groups (grafting rate of isocyanate groups: 64%);
[0084] S2, dissolving 4.76g of amino-terminated hyperbranched polylysine (1.36mmol) in 150mL of deionized water to obtain an amino-terminated hyperbranched polylysine solution; immersing the wool nylon fabric with isocyanate groups grafted on the surface in step S1 in the above solution, treating at 60°C for 1h, drying at 80°C for 30min, and baking at 110°C for 10min to obtain an amino-terminated hyperbranched polylysine modified wool fabric;
[0085] S3, 4.1g 2,3-epoxypropyltrimethylammonium chloride (27mmol) was dissolved in 150mL deionized water to obtain an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride, and the wool fabric modified with hyperbranched polylysine in step S2 was immersed in the above solution, treated at 60°C for 1h, and finally dried at 80°C for 30min and baked at 110°C for 10min to obtain the wool fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt.
[0086] The test results are as follows: the wool fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared in this embodiment has an antibacterial rate of 99.97% against Escherichia coli and Staphylococcus aureus before washing, and the antibacterial rate remains at 99.4% after washing 50 times. After washing 50 times, the antiviral activity rate against influenza A virus reaches 99.11%. This shows that the wool fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared by the method of this embodiment has excellent antibacterial and antiviral properties, and has good durability.
[0087] Example 4
[0088] The preparation method of this embodiment comprises the following steps:
[0089] S1. 3 g of isocyanate propyl triethoxysilane was added to 100 mL of ethanol solution and mechanically stirred for 10 min to obtain an ethanol solution of isocyanate propyl triethoxysilane; 3 g of polycaprolactone fabric was immersed in the mixed solution, and 50 mL of deionized water was added after sufficient stirring for 10 min; the polycaprolactone fabric was fully treated at 60° C. for 1 h, dried at 80° C. for 30 min, and baked at 110° C. for 10 min to obtain an isocyanate group-modified polycaprolactone fabric (with an isocyanate group grafting rate of 67%);
[0090] S2, dissolving 3g of hyperbranched lysine-arginine copolymer (0.27mmol, molecular weight 11000) in 150mL of deionized water to obtain a hyperbranched lysine-arginine copolymer solution; immersing the fabric modified with isocyanate groups in step S1 in the above solution, treating at 60°C for 1h, drying at 80°C for 30min, and baking at 110°C for 10min to obtain a hyperbranched lysine-arginine copolymer-modified polycaprolactone fabric;
[0091] S3, 1.52g 2,3-epoxypropyltrimethylammonium chloride (10mmol) was dissolved in 150mL deionized water to obtain an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride, and the fabric modified with the hyperbranched lysine-arginine copolymer in step S2 was immersed in the above solution, treated at 40°C for 1h, and finally dried at 80°C for 30min and baked at 110°C for 10min to obtain a polycaprolactone fabric modified with a quaternary ammonium salt of a hyperbranched lysine-arginine copolymer.
[0092] The test results are as follows: the antibacterial rate of the hyperbranched lysine-arginine copolymer quaternary ammonium salt-modified polycaprolactone fabric prepared in this embodiment against Escherichia coli and Staphylococcus aureus can reach 99.96% before washing; after washing 50 times, the antibacterial rate is still maintained at 99.31%. After washing 50 times, the antiviral activity rate of the hyperbranched lysine-arginine copolymer quaternary ammonium salt-modified polycaprolactone fabric prepared in this embodiment against influenza A virus reaches 98.8%. This shows that the hyperbranched lysine-arginine copolymer quaternary ammonium salt-modified polycaprolactone fabric prepared by the method of this embodiment has excellent antibacterial and antiviral properties, and has good durability.
[0093] Example 5
[0094] The preparation method of this embodiment comprises the following steps:
[0095] S1. Take 3g of isocyanate propyl triethoxysilane and add it to 100mL of ethanol solution, and stir it mechanically for 10min to obtain an ethanol solution of isocyanate propyl triethoxysilane; immerse 3g of polylactic acid fabric in the mixed solution, stir it thoroughly for 10min, then add 50mL of deionized water, and finally heat the solution to 60°C and keep it warm for 1h; after the reaction is completed, take out the fabric by padding, dry it at 80°C for 30min, and bake it at 110°C for 10min, to obtain a polylactic acid fabric with isocyanate groups grafted on the surface (the grafting rate of isocyanate groups is 63%);
[0096] S2, dissolving 4.76g of amino-terminated hyperbranched polylysine (1.36mmol) in 150mL of deionized water to obtain an amino-terminated hyperbranched polylysine solution; immersing the polylactic acid fabric with isocyanate groups grafted on the surface in step S1 in the above solution, reacting at 60°C for 1h, drying at 80°C for 30min, and baking at 110°C for 10min to obtain an amino-terminated hyperbranched polylysine modified polylactic acid fabric;
[0097] S3, dissolving 4.2g 2,3-epoxypropyltrimethylammonium chloride (28mmol) in 150mL deionized water to obtain an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride, immersing the polylactic acid fabric modified with hyperbranched polylysine in step S2 in the above solution, reacting at 60°C for 1h, and finally drying at 80°C for 30min and baking at 110°C for 10min to obtain the polylactic acid fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt.
[0098] Figure 5 This is an infrared image of the hyperbranched poly-lysine quaternary ammonium salt-modified polylactic acid fabric prepared in Example 5. Figure 5 It can be seen that after the treatment, amide A, amide I and amide II appeared in the infrared spectrum of the fabric, and 2866 cm -1 A new CH absorption peak appeared at , which indicated that hyperbranched poly-lysine was grafted onto the surface of polylactic acid fabric.
[0099] The test results are as follows: the polylactic acid fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared in this embodiment has an antibacterial rate of 99.9% against Escherichia coli and Staphylococcus aureus before washing, and the antibacterial rate remains at 99.12% after washing 50 times. After washing 50 times, the antiviral activity rate of the above fabric against influenza A virus reaches 98.42%. This shows that the polylactic acid fabric modified with terminal amino hyperbranched polylysine quaternary ammonium salt prepared by the method of this embodiment has excellent antibacterial and antiviral properties, and has good durability.
[0100] Figure 6In the figure, (a) and (b) are SEM images of the raw material polylactic acid fabric and the polylactic acid fabric modified with hyperbranched polylysine quaternary ammonium salt, respectively. By comparison, it can be seen that the surface of the untreated polylactic acid fiber is smooth and there is no adhesion between the fibers; while the surface of the lactic acid fiber modified with hyperbranched polylysine quaternary ammonium salt has the same smoothness, the difference is that a cross-linked film appears between the polylactic acid fibers, and it is obvious that the film structure comes from the hyperbranched polylysine quaternary ammonium salt.
Claims
1. A method for preparing a completely degradable antibacterial, antiviral and wash-resistant fabric, characterized in that: The preparation method comprises the following steps: S1, dissolving a siloxane coupling agent with an isocyanate group in an organic solvent to obtain a siloxane coupling agent solution, then immersing a fabric in the siloxane coupling agent solution, adding water for treatment, and then drying to obtain a fabric with an isocyanate group grafted on the surface; S2, dissolving a hyperbranched polymer in water to obtain a hyperbranched polymer solution, immersing the fabric with the surface grafted with isocyanate groups in the hyperbranched polymer solution for treatment, and then drying to obtain a fabric modified with the hyperbranched polymer; S3, take alkoxy quaternary ammonium salt and dissolve it in water to obtain an aqueous solution of alkoxy quaternary ammonium salt, immerse the fabric modified by the hyperbranched polymer in the aqueous solution of the alkoxy quaternary ammonium salt for treatment, and then dry to finally obtain the fabric modified by the hyperbranched polymer quaternary ammonium salt, wherein the fabric is selected from cotton, silk, wool, polylactic acid fabric, polycaprolactone fabric and two or more blended fabrics thereof.
2. The preparation method according to claim 1, characterized in that: In step S1, the siloxane coupling agent with an isocyanate group is one or more of isocyanatepropyltrimethoxysilane, isocyanatepropylmethyldiethoxysilane, isocyanatepropylmethyldimethoxysilane, diisocyanatedimethylsilane and isocyanatepropyltriethoxysilane; and / or the organic solvent is an alcohol solvent.
3. The preparation method according to claim 2, characterized in that: In step S1, the siloxane coupling agent with an isocyanate group is isocyanate propyl triethoxy silane; and / or the organic solvent is methanol and / or ethanol.
4. The preparation method according to claim 3, characterized in that: In step S1, the organic solvent is ethanol.
5. The preparation method according to any one of claims 2 to 4, characterized in that: In step S1, the concentration of the siloxane coupling agent in the siloxane coupling agent solution is 0.1-10 wt %.
6. The preparation method according to claim 5, characterized in that: In step S1, the concentration of the siloxane coupling agent in the siloxane coupling agent solution is 0.5-5wt%.
7. The preparation method according to claim 6, characterized in that: In step S1, the concentration of the siloxane coupling agent in the siloxane coupling agent solution is 3-4 wt%.
8. The preparation method according to any one of claims 1 to 3, characterized in that: In step S1, the treatment temperature is 20-90°C; the treatment time is 10-180 min; and / or, in step S1, the volume ratio of water to the organic solvent is 1:1-1:
5.
9. The preparation method according to claim 8, characterized in that: In step S1, the treatment temperature is 30-80°C; the treatment time is 20-120 min; and / or, in step S1, the volume ratio of water to the organic solvent is 1:1-1:
4.
10. The preparation method according to claim 9, characterized in that: In step S1, the treatment temperature is 50-60°C; the treatment time is 30-90 min; and / or, in step S1, the volume ratio of water to the organic solvent is 1:1.5-1:2.
5.
11. The preparation method according to claim 10, characterized in that: In step S1, the treatment time is 60 min; and / or, in step S1, the volume ratio of water to the organic solvent is 1:
2.
12. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the hyperbranched polymer is a degradable hyperbranched polymer, and the degradable hyperbranched polymer is selected from one or more of hyperbranched polylysine, hyperbranched lysine-arginine copolymer, and β-cyclodextrin grafted hyperbranched polyglycidyl ether, and the weight average molecular weight of the hyperbranched polymer is 1500 to 13000.
13. The preparation method according to claim 12, characterized in that: In step S2, the hyperbranched polymer is amino-terminated hyperbranched polylysine and / or a hyperbranched lysine-arginine copolymer, and the weight average molecular weight of the hyperbranched polymer is 2000-11000.
14. The preparation method according to claim 13, characterized in that: In step S2, the weight average molecular weight of the hyperbranched polymer is 8000-11000.
15. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the concentration of the hyperbranched polymer in the hyperbranched polymer solution is 0.1-15 wt %.
16. The preparation method according to claim 15, characterized in that: In step S2, the concentration of the hyperbranched polymer in the hyperbranched polymer solution is 0.5-5wt%.
17. The preparation method according to claim 16, characterized in that: In step S2, the concentration of the hyperbranched polymer in the hyperbranched polymer solution is 1-3 wt %.
18. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the treatment temperature is 30-110° C., and the treatment time is 10-180 min; and / or the bath ratio of the fabric with surface grafted isocyanate groups and the hyperbranched polymer solution is 0.1:50-5:
50.
19. The preparation method according to claim 18, characterized in that: In step S2, the treatment temperature is 40-90°C, and the treatment time is 20-120 min; and / or the bath ratio of the fabric with surface grafted isocyanate groups and the hyperbranched polymer solution is 0.5:50-2:
50.
20. The preparation method according to claim 19, characterized in that: In step S2, the treatment temperature is 50-70° C., and the treatment time is 30-90 min; and / or the bath ratio of the fabric with surface grafted isocyanate groups to the hyperbranched polymer solution is 1:
50.
21. The preparation method according to claim 20, characterized in that: In step S2, the treatment temperature is 60°C and the treatment time is 60 minutes.
22. The preparation method according to any one of claims 1 to 4, characterized in that: In step S3, the alkoxy quaternary ammonium salt is selected from 2,3-epoxypropyltrimethylammonium chloride and / or 2,3-epoxybutyltrimethylammonium chloride.
23. The preparation method according to claim 22, characterized in that: In step S3, the alkoxy quaternary ammonium salt is 2,3-epoxypropyltrimethylammonium chloride.
24. The preparation method according to any one of claims 1 to 4, characterized in that: In step S3, the concentration of the alkoxy quaternary ammonium salt in the aqueous solution of the alkoxy quaternary ammonium salt is 0.1 to 15 wt %; and / or, The molar ratio of the alkoxy quaternary ammonium salt in step S3 to the hyperbranched polymer in step S2 is 100:1 to 2:1; and / or, In step S3, the treatment temperature is 30-110° C. and the treatment time is 10-180 min; and / or, In step S3, the bath ratio of the hyperbranched polymer-modified fabric to the aqueous solution of the alkoxy quaternary ammonium salt is 0.1:50 to 5:50; and / or In step S1, step S2 and step S3, the drying includes drying at 50-100° C. for 10 minutes to 1 hour and baking at 100-120° C. for 1-30 minutes.
25. The preparation method according to claim 24, characterized in that: In step S3, the concentration of the alkoxy quaternary ammonium salt in the aqueous solution of the alkoxy quaternary ammonium salt is 0.5-5wt%; and / or, The molar ratio of the alkoxy quaternary ammonium salt in step S3 to the hyperbranched polymer in step S2 is 50:1 to 10:1; and / or, In step S3, the treatment temperature is 35-80° C. and the treatment time is 20-120 min; and / or, In step S3, the bath ratio of the hyperbranched polymer-modified fabric and the aqueous solution of the alkoxy quaternary ammonium salt is 0.5:50 to 2:50; and / or In step S1, step S2 and step S3, the drying includes drying at 60-90° C. for 20-50 minutes and baking at 105-110° C. for 5-20 minutes.
26. The preparation method according to claim 25, characterized in that: In step S3, the concentration of the alkoxy quaternary ammonium salt in the aqueous solution of the alkoxy quaternary ammonium salt is 1-3wt%; and / or, The molar ratio of the alkoxy quaternary ammonium salt in step S3 to the hyperbranched polymer in step S2 is 40:1 to 15:1; and / or, In step S3, the treatment temperature is 40-60° C. and the treatment time is 30-90 min; and / or, In step S3, the bath ratio of the hyperbranched polymer-modified fabric to the aqueous solution of the alkoxy quaternary ammonium salt is 1:50; and / or In step S1, step S2 and step S3, the drying includes drying at 70-80° C. for 25-40 minutes and baking at 105-110° C. for 8-12 minutes.
27. The preparation method according to claim 26, characterized in that: In step S3, the processing time is 60 minutes.
28. The antibacterial, antiviral and wash-resistant fabric prepared by the preparation method according to any one of claims 1 to 27.
Citation Information
Patent Citations
Hyperbranched antibacterial polyurethane reverse osmosis membrane and preparation method thereof
CN113663539A
Method for preparing environmentally friendly surface-modified cotton fiber
WO2022067886A1
Cited By
Degradable three-proofing fabric
CN224378576U